2017
DOI: 10.3390/su9030353
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Monitoring and Management Systems for Improving Sustainability in Precision Irrigation

Abstract: Globally, the irrigation of crops is the largest consumptive user of fresh water. Water scarcity is increasing worldwide, resulting in tighter regulation of its use for agriculture. This necessitates the development of irrigation practices that are more efficient in the use of water but do not compromise crop quality and yield. Precision irrigation already achieves this goal, in part. The goal of precision irrigation is to accurately supply the crop water need in a timely manner and as spatially uniformly as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(100 citation statements)
references
References 114 publications
(157 reference statements)
1
75
0
1
Order By: Relevance
“…This is surprising as there is now a global trend towards the development of precision irrigation technology [99]. Ultimately, precision irrigation technology drives water use efficiency by carefully targeting moisture application directly to the needs of individual plants rather than for a whole crop.…”
Section: Water and Agriculturementioning
confidence: 95%
“…This is surprising as there is now a global trend towards the development of precision irrigation technology [99]. Ultimately, precision irrigation technology drives water use efficiency by carefully targeting moisture application directly to the needs of individual plants rather than for a whole crop.…”
Section: Water and Agriculturementioning
confidence: 95%
“…Another attempt to improve WP is deficit irrigation (DI) which may be defined as the application of irrigation below crop water requirements [6]. Numerous studies have shown the benefits of DI on improving WP [7,8]. However, DI is not necessarily beneficial as it is quite difficult to know in prior the optimum percentage of ET deficit which differs from one combination of soil, crop, and climate to another.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the National Pollution Inventory (NPI) (2014) reported that H 2 S is emitted from electric power plants, burning of coal or fuel oil containing sulphur, from coke ovens, geothermal power plants, breweries, car exhausts, and septic tanks, among others. Adeyemi (2009) reported that the Nigerian Breweries PLC (NBPLC) uses diesel, low pour fuel oil (LPFO) and …”
Section: Discussionmentioning
confidence: 99%